PENGARUH MOTIVASI DAN KEPUASAN TERHADAP KINERJA KARYAWAN BAZNAS JATIM - Baihaqi, Riksan; Rachmawati, Lucky (Jurnal Ekonomika dan Bisnis Islam, 2020)
The purpose of this study is to see how big the influence of motivation (X1) and satisfaction employee (X2) on the performance of employee (Y) is based on the gaps that occur in the field  BAZNAS the Province of east Java . In this study, the method used is quantitative by using the explanotary reseach approaches. Respondents who used amounted to 32 people. For data collection using online questionnaire or google form with the size of the likert scale t to employees BAZNAS the Province of East Java and the test conducted using test instruments that test the validity and reliability. Analysis techniques using multiple linear regression analysis and hypothesis test. The results of data processing of this research is motivation significant effect on employee performance with a value of 1% < 5% and tcount (2.760) > ttable (2,160) and satisfaction employee significantly effect the performance of employees with a value of 0% < 5% and tcount (4.856) > ttable ( 2,160) as well as the results of R2 is 53.2% of the remaining 46,8% influenced by other variables.